2021
DOI: 10.2174/1570162x19666210423124839
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of a HIV Positive Patient Infected with COVID-19 After an Autologous Bone Marrow Transplantation: A Case Report

Abstract: Background: The World Health Organization (WHO) announced the SARS-COV-2 disease pandemic on March 9, 2020.With the advent of this disease, another health burden was added to about 37.9 million people in the world who are infected with HIV and are suffering from various diseases. These people may be at serious risk of covid-19. Information about the effects of Covid-19 on people living with HIV, is limited. Case presentation: We reported a 61-year-old man who was a known case of HIV from 6 years ago that wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Neurologic symptoms of COVID-19 have been reported since the outbreak of the pandemic (3). Nonspecific neurologic symptoms (such as headache, dizziness, and seizure) can be associated with this disease (6,13). This study suggested that 67% of patients with COVID-19 had at least one of the neurological symptoms.…”
Section: Discussionmentioning
confidence: 72%
“…Neurologic symptoms of COVID-19 have been reported since the outbreak of the pandemic (3). Nonspecific neurologic symptoms (such as headache, dizziness, and seizure) can be associated with this disease (6,13). This study suggested that 67% of patients with COVID-19 had at least one of the neurological symptoms.…”
Section: Discussionmentioning
confidence: 72%